Wireless Sensors and Instruments: Networks, Design, and Applications (CRC Press, 2009)
Advances such as 3-G mobile communications networks demonstrate the increasing capability of high-quality data transmission over wireless media. Adapting wireless functionality into instrument and sensor systems endows them with unmatched flexibility, robustness, and intelligence. Wireless Sensors and Instruments: Networks, Design, and Applications explains the principles, state-of-the-art technologies, and modern applications of this burgeoning field.